Nghiên cứu phản ứng trans-este hóa trong sự có mặt của xúc tác chất lỏng ion - Nam Bình, Phạm Thị; Thúy Hạnh, Đặng Thị; Thu Hà, Vũ Thị; Hải, Đỗ Thanh; Hiếu, Trần Văn (Vietnam Journal of Chemistry, 2015)
Transesterification reaction between refined coconut oil and methanol was investigated in the present of ionic liquid 1-(4-sulfonic acid) butyl-3-methylimidazolium methane sulfonate as catalyst. The results show that the methyl esters content of product exceeds 88 % at 75 oC for 8 hours with methanol/oil/catalyst molar ratio of 12:1:0.15. This catalyst can be recovered and reused. So it has potential application in transesterification process.